Indigenous Musical Instruments as Ethno-STEM Catalysts for Enhancing Scientific Literacy Through Cultural Integration - Henie Poerwandar Asmaningrum; Anastasia Elvi Gleko; Renuka V Sathasivam; Novike Bela Sumanik (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: Investigated the effectiveness of a Tifa drum-based Ethno-STEM instructional approach on enhancing scientific literacy among secondary school students, specifically examining how indigenous cultural artifacts can serve as bridges between traditional knowledge systems and Western scientific understanding. Methodology: A true experimental design with pretest-posttest control group was employed with 40 eighth-grade students randomly assigned to experimental (n=20) or control (n=20) groups. The experimental group received nine weeks of instruction using the HENIE syntax (Highlighting, Exploring, Narrating, Implementing, Evaluating) to integrate Tifa drum knowledge with vibration, waves, and sound concepts. The control group received conventional instruction. Scientific literacy was measured across three dimensions: content, procedural, and epistemic knowledge using a validated 25-item assessment instrument. Main Findings: The Tifa-based Ethno-STEM approach demonstrated significantly superior outcomes compared to traditional instruction. The experimental group achieved higher normalized learning gains (0.48 vs. 0.31) with a large effect size (Cohen's d = 0.84, p < 0.001). Most notably, the epistemic dimension showed the largest improvement differential (77% vs. 60%), while content and procedural dimensions improved from low to moderate proficiency levels. Student responses indicated high engagement, cultural pride, and enhanced conceptual accessibility. The HENIE model successfully bridges indigenous and scientific knowledge systems, particularly strengthening epistemic understanding—a critical yet often neglected component of scientific literacy. Novelty/Originality of this study: This study pioneers the quantitative validation of indigenous musical instruments as effective STEM learning tools, introducing the transferable HENIE pedagogical syntax that demonstrates how cultural artifacts can specifically enhance epistemic scientific literacy development.